Broiler Carcasses Performance at Different Age of Slaughtering - Riyanti, Riyanti (ANIMAL PRODUCTION, 2006)
The objective of this experiment was to determine broiler carcass performance slaughtered at different ages. Seventy-two broilers CP 707 slaughtered at 4, 5, and 6 weeks were used in this experiment. Each treatment had eight replication and each replication used three broiler. The results showed that age of slaughtering have significant effectÂ  (P<0.05) on carcass weight, and high significant effect (P<0.01) to tear skin, bruises skin, misplaced bone and meat tenderness, but has no significant effect (P>0.05) on broken bone. (Animal Production 8(3): 211-215 (2006)Â Key Words: Broiler, carcass, slaughtering, age